The Creativity of Islamic Religious Education Teachers in Improving Student Learning Atmosphere at Junior High School in Jambi - Frensilia, Nina; Huda, Syamsul; Rianty, Ida (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2023)
This study aims to determine the creativity of Islamic religion teachers to improve students' learning atmosphere in the cognitive, affective, and psychomotor domains during the Covid-19 pandemic. This research uses a qualitative approach using a snowball sampling technique. Data collection techniques were carried out using observation, interview, and documentation techniques. The results of this study indicate that the innovations made in improving cognitive, affective, and psychomotor abilities include teachers applying the quiz game of throwing paper balls to create a fun atmosphere. Teachers also take a scientific approach, provide motivation, are good student role models, and hold routine religious activities. Factors that support teacher innovation are internal factors of teacher awareness and external factors of teacher educational background and school contributions. Although limited facilities hinder innovation, the school plans the budget gradually to procure the required facilities through the operational assistance fund.